"Are You There, Trademark Law? It's Me, Misogyny." - Bartow, Ann (Columbia Journal of Gender and Law, 2021)
When I became aware of the emergent body of legal scholarship on menstruation related topics on which this Symposium builds, I thought that the authors of these articles were very brave.1 I’m an imperfect but life-long feminist and accepted the emotional challenge that writing this Essay posed for me out of gratitude to those authors. Because my principal scholarly focus is intellectual property law, I approached the topic through the lens of trademark law. Part One of this article positions this Essay firmly within the contours of the author’s life and personal experiences with menstruation. Part Two maps common trademark and branding practices related to tampons and sanitary napkins. Part Three explains that the Lanham Act does not offer legal mechanisms by which to challenge the federal registration of sexist trademarks. As with racist trademarks, amplified criticism and persistent public pressure are the main mechanisms available to foment positive change in the marketplace for feminine hygiene products.